2006
DOI: 10.1002/ppul.20545
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in sex specific prevalence rates for childhood asthma, eczema, and hay fever

Abstract: The Ceprano calvarium represents one of the most important sources of information about both the dynamics of the earliest hominid dispersal toward Europe and the evolution of the genus Homo in the early‐to‐middle Pleistocene. In this paper, the midsagittal vault profile and the 3D frontal bone morphology of Ceprano are investigated comparatively, using landmark coordinates and Procrustes superimposition. In fact, despite the fact that the skull appears partially distorted by diagenetic pressures (thus precludi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
55
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 39 publications
9
55
4
2
Order By: Relevance
“…10 Between the ages of 9 and 11 years, the difference in the prevalence of asthma between boys and girls disappeared. 39 In agreement with these results, we found no difference in the prevalence of asthma between boys and girls at a mean age of 11.1 years. Nicolai et al 3 followed up adolescents with asthma from the age of 10 years until 14 years.…”
Section: Discussionsupporting
confidence: 91%
“…10 Between the ages of 9 and 11 years, the difference in the prevalence of asthma between boys and girls disappeared. 39 In agreement with these results, we found no difference in the prevalence of asthma between boys and girls at a mean age of 11.1 years. Nicolai et al 3 followed up adolescents with asthma from the age of 10 years until 14 years.…”
Section: Discussionsupporting
confidence: 91%
“…15 The few studies that have focused on the separate contributions of atopic versus nonatopic asthma on prevalence time trends have reached conflicting conclusions. [22][23][24] In addition, the Phase II ISAAC study showed that the link between atopic sensitization and asthma symptoms differs strongly between populations and increases with economic development. 25 Regarding the influence of sex on the prevalence of childhood asthma, early studies reported a male/female ratio of ϳ2:1.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with students in 1984,1994,1999 and 2004 by Osman et al 14 found higher prevalences and time trends of asthma in males. In children, the highest prevalences of asthma in males, when compared to females, can be explained by physiological disadvantages.…”
Section: Discussionmentioning
confidence: 99%